Evaluation of the Effects of Body Forces and Diffusion Mechanisms on Droplet Separation in a Two-Phase Annular–Mist Flow - Oktawia Dolna (Applied Sciences)
For decades, studies have been conducted on the efficiency of gas purification processes with wet scrubbers, including the Venturi scrubbers, and this is the most commonly addressed issue in the field literature. The Venturi scrubber consists of a Venturi nozzle and a cyclone. The article addresses the empirical and analytical studies on the annular–mist flow regime that exists in the throat of the Venturi nozzle with a square cross-section. The uniform distribution of droplets over the cross-section area of the Venturi’s throat strongly correlates with the efficiency of the gas cleaning process using Venturi scrubbers. Due to the above, studies on the physics of the phenomena that affect the quantity of small droplets present in the core of the flow are highly justified. The influence of body forces and diffusive mechanisms impacting the number of droplets in the core flow were investigated to tackle the problem in question. Consequently, the fractions of droplets susceptible to turbulent or inertial–turbulent diffusion mechanisms can now be predicted using the outcomes of the research carried out. The droplets were divided into three fractions that differed by their sizes as follows: airborne droplets I confirm thar italic can be removed in all cases. <semantics>(dd≤</semantics> 10 µm), medium-sized droplets <semantics>(dd<mspace width="3.33333pt"></mspace>≤</semantics> 20 µm), and largest droplets <semantics>(dd</semantics> = (50–150) µm). The estimation of diffusion coefficients <semantics><mfenced separators="" open="(" close=")">εd,M,εd,ref</mfenced></semantics> and stopping distances <semantics><mfenced separators="" open="(" close=")">sM,sref</mfenced></semantics> of all fractions of droplets was carried out with the inclusion <semantics><mfenced separators="" open="(" close=")">εd,M,sM</mfenced></semantics> and exclusion <semantics><mfenced separators="" open="(" close=")">εd,ref,sref</mfenced></semantics> of the Magnus lift force <semantics><mfenced open="(" close=")">M</mfenced></semantics> in equations of both the droplet’s stopping distance and its diffusion coefficient. The outcomes revealed that the inclusion of the M force translates significantly to the growth in values of <semantics>εd,M,sM</semantics> compared to <semantics>εd,ref,sref</semantics>. Hence, it was concluded that the M force impacts the increase in the speed of the diffusion of the droplets with <semantics>dd≥</semantics> 16.45 µm, which is favorable. Hence, the inertial–turbulent diffusion of larger droplets and the turbulent diffusion of medium ones seem to be supported by the M force. The local velocity gradient, which varied within the region of the flow’s hydraulic stabilization also impacted the mass content of droplets with diameter <semantics>dd<mspace width="3.33333pt"></mspace>≤</semantics> 10 µm in the core of the flow. As the flow development progressed, the number of droplets measured at n = 5 Hz varied nonlinearly up to the point where the boundary layer thickness reached the channel radius. The quantity of small droplets in the main flow was significantly influenced by turbulence intensity <semantics>(Tu)</semantics>. The desired high number of small droplets in the core of the flow (mist flow) was estimated empirically, and it was achieved when gas flows at high speed and has a mean value of Tu. The former benefits the efficiency of gas purification. Investigations on the effects of body forces of inertia of the continuous phase on the separation of droplets with diameters of a few microns and sub-microns from the flow were performed by employing two channel elbows, namely <semantics>e4</semantics> and <semantics>e1</semantics>. The curved channels were subsequently mounted at the end of the straight channel (<semantics>SCh2</semantics>). The curvature angle (<semantics>α</semantics>) of the <semantics>e4</semantics> and <semantics>e1</semantics> equaled 90 °C and 30 °C, respectively. The number of droplets existing in the mist flow was higher in value, as desired, when the <semantics>e4</semantics> was used, unlike <semantics>e1</semantics>. Two-dimensional flow fields of the mist have been obtained using the Particle Imaging Velocimetry (PIV) technique and analyzed further. Topas LAP 332 Aerosol Spectrometer was used for the determination of droplet (<semantics>dd<mspace width="3.33333pt"></mspace>≤</semantics> 40 µm) size distribution (DSD) and particle concentrations, while the Droplet Size Analyzer D Kamika Instruments (DSA) was exploited to ascertain DSD of droplets with diameter <semantics>dd>40</semantics> µm.